Motivation to participate in a virtual exchange among nursing students with and without prior online course experience: A comparative study - Qowi, Nurul Hikmatul; Martini, Diah Eko; Utomo, Dias Tiara Putri (The Journal of Palembang Nursing Studies, 2024)
Background: Virtual exchange programs offer several benefits, including enhancing students’ knowledge, promoting technological literacy, and fostering cross-cultural exchange between countries. However, student participation in virtual exchanges remains relatively low.Objective: This study aimed to compare the motivation to participate in virtual exchange programs between nursing students with and without prior experience in online courses. Methods: A comparative study design with purposive sampling was used. Nursing students who had previously participated in online courses (n = 53) and those who had not (n = 47) completed a 29-item motivation questionnaire. Data were analyzed using the Mann–Whitney U test to assess differences in motivation between the two groups.Results: Students with prior online course experience demonstrated higher motivation to participate in virtual exchanges (84.8%) compared to those without such experience (70.4%). The Mann–Whitney U test revealed a significant difference in motivation between the two groups (p = 0.003).Conclusion: Online course participation appears to be a motivating factor for nursing students to engage in virtual exchange programs. Encouraging involvement in online learning may serve as an effective strategy to prepare nursing students for future participation in international collaborations and the global healthcare market.